Tetrathiomolybdate Partially Alleviates Erectile Dysfunction of Type 1 Diabetic Rats Through Affecting Ceruloplasmin/eNOS and Inhibiting Corporal Fibrosis and Systemic Inflammation. Issue 1 (21st November 2021) - Yin, Yinghao; Peng, Jingxuan; Zhou, Jun; Chen, Hanfei; Peng, Dongyi; Li, Dongjie; Gan, Yu; Yin, Guangming; Tang, Yuxin
Abstract: Introduction: Patients with erectile dysfunction induced by diabetes mellitus (DMED) show a poor effect rate for oral phosphodiesterase type 5 inhibitors (PDE5is). Therefore, the new therapeutic strategy is necessary in patients with DMED. Aim: To investigate whether Tetrathiomolybdate (TM) supplementation could ameliorate DMED by activation of eNOS. Methods: Twenty-four diabetic rats were induced by intraperitoneal injection of streptozotocin (STZ) and the other 6 normal rats constituted the control group. Eight weeks later, the erectile function of rats was assessed with an apomorphine test. Only some rats with DMED were treated with TM orally every day for 4 weeks; the other rats remained in the same condition for 4 weeks. After 1 week washout, the erectile function of rats in each group was evaluated. Then, the serum concentration of IL-6 and histologic changes of corpus cavernosum were measured. Main Outcome Measure: Erectile function was measured after DMED rats treated with TM. The cavernosum level of Ceruloplasmin (Cp), eNOS, endothelial cell content, corporal fibrosis, apoptosis rate and the serum level of IL-6 were also assayed. Results: Erectile function in the DMED group was significantly impaired compared with the control group and was partly, but significantly, improved in the DMED+TM group. The DMED group showed upregulation of Cp and inhibition of eNOS, but the inhibition was partly reversed in the DMED+TM group. The DMED group showed serious corporal fibrosis. However, TM supplementation partly increased the ratio of smooth muscle to collagen, decreased the ratio of apoptosis. What's more, gavage administration of TM profoundly decreased the serum level of IL-6 in DMED rats. Conclusion: TM supplementation inhibits endothelial dysfunction, corporal fibrosis, and systemic inflammation, ultimately leading to partial improvement of DMED in rats.